2017
DOI: 10.1111/dom.13012
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporter‐2 inhibitors and diabetic ketoacidosis: An updated review of the literature

Abstract: Sodium-glucose cotransporter-2 inhibitors (SGLT2is) are increasingly used for the treatment of type 2 diabetes (T2D) and can improve glucose control also in type 1 diabetes (T1D). In May 2015, regulatory agencies issued a warning that SGLT2is may cause diabetic ketoacidosis (DKA). We report details on 2 new cases of SGLT2i-associated DKA and review the literature for similar cases within randomized controlled trials (RCTs), cohort studies and single reports. We searched the medical literature for reports of SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 64 publications
2
71
1
4
Order By: Relevance
“…A recent literature review analysed RCTs, cohort studies, case reports and pharmacovigilance database studies53: DKA incidence was less than 1/1000 in RCTs (in line with data from an MA54) and 1.6/1000 person‐years in cohort studies. In case reports and in pharmacovigilance databases, duration of SGLT2‐I treatment before DKA onset was extremely variable; overall, DKA is a rare adverse event during SGLT2‐I therapy, with fatal episodes representing 1.6% of all reported cases 55.…”
Section: Observational Findings: What's Missing?mentioning
confidence: 70%
“…A recent literature review analysed RCTs, cohort studies, case reports and pharmacovigilance database studies53: DKA incidence was less than 1/1000 in RCTs (in line with data from an MA54) and 1.6/1000 person‐years in cohort studies. In case reports and in pharmacovigilance databases, duration of SGLT2‐I treatment before DKA onset was extremely variable; overall, DKA is a rare adverse event during SGLT2‐I therapy, with fatal episodes representing 1.6% of all reported cases 55.…”
Section: Observational Findings: What's Missing?mentioning
confidence: 70%
“…Importantly, when DKA does occur in patients taking SGLT2 inhibitors, it often presents with an uncommon feature. Whereas DKA without hyperglycemia, or euglycemic DKA, has long been recognized as a rare condition overall, it occurs not so infrequently in individuals taking SGLT2 inhibitors, with 30–50% of DKA cases taking this form in patients on these drugs. Given the lack of symptoms related to hyperglycemia, it is often difficult to notice the development of euglycemic DKA.…”
Section: Cases Of Diabetic Ketoacidosis In Type 1 Diabetes Patients Tmentioning
confidence: 99%
“…However, such patients are at a higher risk for DKA than are type 2 diabetes patients. Whereas the incidence of SGLT2 inhibitor‐related DKA was <0.1% in randomized controlled trials with type 2 diabetes patients, the incidence increased to ~4–6% in those with type 1 diabetes. Furthermore, a meta‐analysis showed that the administration of SGLT2 inhibitors significantly increases the incidence of DKA in patients with type 1 diabetes.…”
Section: Cases Of Diabetic Ketoacidosis In Type 1 Diabetes Patients Tmentioning
confidence: 99%
“…In 2015, the Food and Drug Administration cautioned that SGLT2 inhibitors may increase the risk of ketoacidosis based on 20 cases . The European Medicines Agency subsequently reported 147 cases of ketoacidosis associated with SGLT2 inhibitors . The type‐2 diabetes clinical trials for canagliflozin, dapagliflozin and empagliflozin have accumulated 44,000 patient years of exposure to SGLT2 inhibitors with diabetic ketoacidosis incidence rates varying from 0.16 to 0.76 event per 1000 patient years .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment consists of stopping the SGLT2 inhibitor, intravenous fluids, insulin and occasionally bicarbonate . Sodium‐glucose co‐transporter type 2 inhibitors compound the hypovolaemia that results from diabetic ketoacidosis and thus large volumes of normal saline may be required. An insulin infusion at a lower‐than‐usual rate of 0.05 units.kg.h ‐1 with an infusion of dextrose‐5% and normal saline is indicated if the patient is euglycaemic .…”
Section: Introductionmentioning
confidence: 99%